2018
DOI: 10.1016/j.chempr.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Graphitized Carbon Nanohorns as a Forefront Electrocatalyst in Highly Selective O2 Reduction to H2O2

Abstract: Fornasiero and colleagues describe an alternative strategy for producing hydrogen peroxide through a more sustainable method than the current synthetic approaches. The strategy relies on the use of electrocatalysis, made possible by the use of a catalyst with high efficiency and selectivity toward H 2 O 2 formation. The prepared material is particularly appealing because it does not contain any metal, implying a greener and cheaper synthetic scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
331
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(341 citation statements)
references
References 47 publications
9
331
0
1
Order By: Relevance
“…Interestingly, the two binding energies at 400.6 and 398.6 eV relate to the sole formation of pyrrolic (C−N bonds) and pyridinic (C=N bonds) N atoms, respectively, with the absence of quaternary or oxidized N atoms. We have recently reported that the exclusive presence of these two types of N atoms in a metal‐free electrocatalyst and their relative ratio (N pyridinic /N pyrrolic =0.89) is instrumental to trigger an almost totally selective two‐electron mechanism under acidic conditions . The N pyridinic /N pyrrolic atomic ratio for Co‐NC‐im is 0.83, thus confirming the key importance of this parameter (Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the two binding energies at 400.6 and 398.6 eV relate to the sole formation of pyrrolic (C−N bonds) and pyridinic (C=N bonds) N atoms, respectively, with the absence of quaternary or oxidized N atoms. We have recently reported that the exclusive presence of these two types of N atoms in a metal‐free electrocatalyst and their relative ratio (N pyridinic /N pyrrolic =0.89) is instrumental to trigger an almost totally selective two‐electron mechanism under acidic conditions . The N pyridinic /N pyrrolic atomic ratio for Co‐NC‐im is 0.83, thus confirming the key importance of this parameter (Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] Industrially, H 2 O 2 is prepared by direct oxidation of H 2 , which is however with the danger of explosion. [ 9,10 ] O 2 reduction reaction (ORR) represents an attractive alternative to prepare H 2 O 2 with the feature of environmentally friendly and safe, but electrocatalysts suffer from high cost, limited selectivity, and/or low activity. [ 1,2,11,12 ] Besides H 2 O 2 , HCOOH, an important intermediate in industry and the chemical fuel in direct HCOOH fuel cells, is a common CO 2 reduction reaction (CO 2 RR) product, [ 13–15 ] but developing the active, selective, durable, and cheap electrocatalysts for CO 2 RR is also very challenging.…”
Section: Figurementioning
confidence: 99%
“…[9] As an efficient liquid oxidant, H 2 O 2 is also an alternative oxidant for fuel cells in special circumstances where air is not available, such as under-water environment. [10][11] Thus, qualitative and quantitative analysis of H 2 O 2 is both an important practical technology and a hot research topic for a variety of research fields. Especially, in biosystem, detecting H 2 O 2 in situ or in a single living cell level is a challenge for bio-detection and could open a door toward real time observation of cellular physiological processes.…”
Section: Electrochemical Detection Of Hydrogen Peroxidementioning
confidence: 99%
“…In addition, H 2 O 2 is an intermediate of O 2 reduction/evolution reactions (ORR/OER) with coupled multi‐electrons, which is very important for the cathodic kinetics of conventional fuel cells and metal‐air batteries . As an efficient liquid oxidant, H 2 O 2 is also an alternative oxidant for fuel cells in special circumstances where air is not available, such as under‐water environment . Thus, qualitative and quantitative analysis of H 2 O 2 is both an important practical technology and a hot research topic for a variety of research fields.…”
Section: Introductionmentioning
confidence: 99%